A influência de variáveis ambientais na distribuição e abundância de Brachycephalus ephippium na Serra do Japi, Jundiaí, São Paulo - Polettini Neto, Alexandre [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The Atlantic forest has a large number of endemic species due to the varieties of environments, altitudes, and climates found along its distribution. The species Brachycephalus ephippium is an example of endemic anuran from this forest formation, occurring in the states of São Paulo, Rio de Janeiro and Minas Gerais, between 750 and 1200 m altitude. This species is abundant in the Serra do Japi, an Atlantic Forest remnant, which houses high biodiversity, located in Jundiaí city, between three big urban centers in the state of São Paulo. This remnant, which has altitude ranging between 700 and 1300 meters, is threatened by global climate changes and, spite of legally protected, by intense pressure of urbanization. The aim of the present study was to verify the association between of environmental variables with the abundance and distribution of B. ephippium in the Serra do Japi. The air relative humidity showed a positive correlation with the presence of B. ephippium individuals and the best model to explain the abundance involved air relative temperature and litter temperature. These results allowed the investigation of the environment use by this species and can be used to provide conservationist actions

A Mata Atlântica apresenta um grande número de espécies endêmicas, devido à variedade de ambientes, altitudes e climas encontrados ao longo de sua extensão. A espécie Brachycephalus ephippium é um exemplo de anuro endêmico dessas florestas, ocorrendo nos estados de São Paulo, Rio de Janeiro e Minas Gerais, em altitudes entre 750 e 1200 m. Essa espécie é abundante na Serra do Japi, um remanescente de Mata Atlântica que abriga elevada biodiversidade, localizado no município de Jundiaí, entre três grandes centros urbanos no estado de São Paulo. Com altitude variando entre 700 e 1300 metros, este remanescente pode estar ameaçado pelas mudanças climáticas globais e, apesar de legalmente protegido, ainda sofre intensa pressão da urbanização. O presente trabalho teve como objetivo verificar a associação de variáveis ambientais com a abundância e distribuição de B. ephippium na Serra do Japi. A umidade relativa do ar apresentou correlação positiva com a presença de indivíduos de B. ephippium e o modelo que melhor explicou a abundância envolveu umidade relativa do ar e temperatura da serapilheira. Estes resultados permitiram a investigação do uso do ambiente por esta espécie e podem ser utilizados para subsidiar medidas conservacionistas
Keywords: Anuro; Anfíbio; Ecologia animal; Anuro - Distribuição geográfica; Adaptação (Biologia); Jundiaí (SP); Japi, Serra do (SP)